Persistent Organic Pollutants (POPs) in the European Union: Analysis of the NORMAN EMPODAT database system - Om Prakash Yadav; Arifur Rahman; Atanu Sarkar; Gopal Achari; Jaroslav Slobodnik (Wolters Kluwer Medknow Publications, 2020)
EMPODAT database is a part of the NORMAN database system based on geo-referenced and biomonitoring and provides information on emerging environmental contaminants in various matrices such as air, water, soil, sewage, sludge, and biota. This database consists of data on newly emerging substances that are known to be present but not yet included in regular chemical monitoring programs. POPs are a global threat to the ecosystem and human health. POPs such as Pre and Perfluorochemicals (PFASs), Polybrominated diphenyl ethers (PBDEs), and Bisphenol A (BPA) are widely present in various environmental matrices and interfere with the normal function of the human body. The proposed research has analyzed the data from the EMPODAT NORMAN database system by focusing on PFASs, PBDEs, and BPA. The study is still ongoing. The data from 28 European countries, including international water, were retrieved and subjected to statistical analysis. The data were arranged according to their specific chemical concentration observed in respective environmental matrices and followed by a recording of fluctuations of these substances in specific time duration and environmental zone. The preliminary analysis shows the individual concentration of chemical substances retrieved from biota (fish, Molluscs, and Macrophytes), surface water (Adriatic Sea, Baltic Sea, Black Sea, Dahle, Danube, Ipel, Spree, Rhine rivers, etc.), groundwater (Adour-Garonne, Artois Picardie, Loire-Bretagne, Rhin-Meuse, Seine-Normandie, and Siverskyi Donets river basins), sediments (Adriatic Sea, Albarine, Anoia, Black sea, Cardener, Danube, North sea, Po, Scheldt estuary, Seine rivers, etc.), sewage sludge (Adour Garonne, Danube, Saronikos gulf river basins, etc.), and wastewater (Brenta, Danube, Itchen, Po, and Saronikos gulf river basins) that were reported over a period of time mostly from 2003 to 2016.